Metacognitive Regulation Strategies for Managing Pedagogical Stress: Implications for Enhancing Teaching Quality In Higher Education - Usmonova Surayyo Muxidinovna (Indonesian Journal Publisher, 2025)
This study investigates the role of metacognitive regulation strategies in managing pedagogical stress and enhancing teaching quality among higher education instructors. The primary aim is to explore how instructors' self-awareness, self-monitoring, and self-control can contribute to reducing stress while fostering instructional effectiveness. Using a qualitative approach supported by surveys, interviews, and classroom observations, the research identifies the most common stressors faced by educators—ranging from institutional demands to student engagement challenges—and how these are mitigated through systematic reflection and adaptive teaching practices. Results demonstrate that instructors who consistently engage in metacognitive strategies such as planning, emotional regulation, and real-time lesson evaluation experience a noticeable decrease in stress levels. Furthermore, these educators report enhanced clarity in communication, improved responsiveness to student needs, and increased professional motivation. The findings highlight that metacognitive regulation not only improves psychological well-being but also drives pedagogical innovation and student satisfaction. Despite its proven benefits, the integration of these strategies into professional development remains limited. Therefore, this study recommends structured training programs and institutional support to embed metacognitive practices within faculty development initiatives, contributing to more sustainable and effective teaching environments in higher education.